Analysis of Socio-Cultural Factors in the Decision Making of Women of Childbearing Age Regarding Reproductive and Sexual Health - Sari, Yulia; Fitriana, Shentya; Hajrah, Wa Ode; Simbolon, Ganda Agustina Hartati (Poltekkes Kemenkes Palu, 2024)
Introduction: The right decision-making process will impact to health status of mothers and children, also to increase the human development index, especially health development in Indonesia. 23% of women said their husbands usually made decisions about household expenses, 11% said their husbands decided on their personal health care. Socio-demographic factors, such as the educational level of husband and wife, economic status are potential factors that can influence an individual's decision-making process. Exposure to information and knowledge, individual abilities can have a positive influence for woman's decision making. It was further stated that a woman's decision making on their sexual and reproductive health is highly dependent on the ability to meet her needs and exposure to knowledge. Objective: This study aims to determine socio-cultural factors on the role of women of childbearing age in making reproductive and sexual health decisions. Method: The research design used cross sectional. The sample calculation uses the lameshow formula for the difference in proportion test with a minimum sample size of 159 women of childbearing age. The sampling technique uses purposive sampling. The analysis used chi square and multiple logistic regression. Results: There is a relationship between socioculture and the role of women in decision making regarding reproductive and sexual health after being controlled by the variables husband's education, mother's education, husband's age, and family income (p = 0.006; OR 2.7' min-max 1.3- 5,6). Conclusion: It is necessary to increase women’s knowledge and their partners regarding gender justice in decision-making autonomy regarding sexual and reproductive health.